Dosing time of ferric chloride to disinhibit the excessive volatile fatty acids in sludge thermophilic anaerobic digestion system. (August 2015) - Yu, Bao; Shan, Aidang; Zhang, Dongling; Lou, Ziyang; Yuan, Haiping; Huang, Xiaoting; Zhu, Nanwen; Hu, Xiaofang
Highlights: Supplementation of FeCl3 could accelerate the hydrolysis–acidification process. The optimum dosing time of FeCl3 is 72nd hour after startup. Acetic acid was the main inhibitor in the thermophilic AD system. FeCl3 contributes to build a favorable condition, except to remove acetic acid. Abstract: An investigation into the effect of ferric chloride (FeCl3 ) on the disinhibition of excessive volatile fatty acids (VFAs) in sludge thermophilic anaerobic digestion (AD) system was performed. The optimum dosing time of FeCl3 was tested with the time interval of 0 h, 36 h, 72 h, 108 h and 144 h. The maximum biogas production was obtained in the case of 72nd hour dosing group, and the biogas production potential was 293.13 ± 11.38 mL/gVS based on modified Gompertz predicted model with the maximum rate of 8.55 ± 0.38 mL/(gVS day), which was triple as that in the control group. More biodegradable organic matters were generated from sludge with FeCl3 additive and then consumed efficiently according to excitation–emission matrix (EEM) fluorescence spectra analysis in the dissolved organic matter (DOM). Acetic acid was the main inhibitor and synthetic effects occurred for the disinhibition of excessive VFAs with the additive of FeCl3, except to direct removal of acetic acid in the system.